Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning Pada Materi Reaksi Reduksi Oksidasi Untuk SMA/MAKelas X - Putri, Siska Triana (RC-INSTITUT, 2019)
This research was a research and development of student worksheet with problem based learning for the Redox Reaction material that has been tested in eleventh grade students of SMA Pembangunan Laboratorium UNP. This study aims to produce the valid and practice of  student worksheet with problem based learning  for the Redox Reaction material. The type of this  is a Research and Development (R & D) and the development model used is a model 4-D consists of four stages; (1) define, (2) design, (3) develop and (4) disseminate. This research is limited to develop stage. The research instrument used a questionnaire validity and practicalities. Validity sheets were filled out by 2 lecturers of department of chemistry and chemical 3 teachers. Practicalities sheets were filled out by 3 people a chemistry teacher and 28 students of class XI SMA Pembangunan Laboratorium UNP. Data from this research will be analyzed using Cohen’s kappa formula. This result found an average value of 0.83 kappa moment with high validity category. This is also found the practicalities of teachers and students an average value moment kappa of 0.83 and 0.81 with high practicality category. This study can be concluded that the student worksheet with problem based learning for the Redox Reaction material is valid and practice, so that it can be used in learning activities.                                           Keywords: Student Worksheets, Problem Based Learning, Redox Reaxtion material, Research and Development, 4-D Models